This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The integral can be solved using differentiation under the integral sign .
I ( a ) ∂ a ∂ I ( a x ) ⟹ I ( a ) I ( 0 ) ⟹ I ( a ) = ∫ − ∞ ∞ x 2 sin 2 ( a x ) d x , = 2 ∫ 0 ∞ x 2 sin 2 ( a x ) d x = 2 ∫ 0 ∞ x 2 2 x sin ( a x ) cos ( a x ) d x = 2 ∫ 0 ∞ x sin ( 2 a x ) d x = 2 ∫ 0 ∞ u sin u d u = 2 Si ( ∞ ) = 2 ⋅ 2 π = π = π a + C = C = 0 = π a Since the integrand is even, Let u = 2 a x ⟹ d u = 2 a d x where Si ( ⋅ ) denotes the sine integral. and Si ( ∞ ) = 2 π where C denotes the constant of integration.
Therefore, I ( 1 ) = ∫ − ∞ ∞ x 2 sin 2 x d x = π ≈ 3 . 1 4